Dioxotriazine derivatives as a new class of P2X3 receptor antagonists: Identification of a lead and initial SAR studies. (1st April 2021) - Kai, Hiroyuki; Horiguchi, Tohru; Kameyama, Takayuki; Asahi, Kentaro; Endoh, Takeshi; Jikihara, Sae; Hasegawa, Tsuyoshi; Tanaka, Satoru; Nozu, Azusa; Takeyama, Chie; Tomari, Maki; Takahashi, Fumiyo; et al.
Graphical abstract: Abstract: P2X3 receptor is an ATP-gated ion channel, mainly localized on peripheral sensory neurons. Currently, several clinical trials are being conducted with P2X3 receptor antagonists for the treatment of chronic pain or cough. To identify a P2X3 lead compound, we reexamined the HTS evaluation compounds and selected dioxotriazine derivatives from which we identified a hit compound. As a result of the hit-to-lead SAR, we obtained lead compound 1 which had a moderate inhibitory effect on P2X3 receptors (IC50, 128 nM). Further improvement of the potency and PK profiles of this lead compound finally led to the selected compound 74 (P2X3 IC50, 16.1 nM; P2X2/3 IC50, 2931 nM), which demonstrated a strong analgesic effect against allodynia on oral administration in the rat partial sciatic nerve ligation model of neuropathic pain (ED50, 3.1 mg/kg).